Contextual Teaching And Learning (CTL) Sebagai Model Pembelajaran Ekonomi dalam KBK - Teguh Sihono (Jurnal Ekonomi dan Pendidikan, 2004)
Curriculum based on competency is a curriculum design developed based on a set of certain competencies. In Indonesia, -so far- education is dominated by idea saying that knowledge is a set of facts that have to be memorized. Classes focus on teacher as a main source of knowledge. It is need to find a new teaching and learning method so that it can develop student involvement. Contextual Teaching and Learning is a new strategy promoted, since this strategy is claimed can encourage students to construct knowledge into their own mind.